Highly sensitive and selective LPG sensor based on alpha-Fe2O3 nanorods - Patil, Dewyani; Patil, Virendra; Patil, Pradip (Sensors and Actuators B-Chemical, 2011)
The alpha-Fe2O3 nanorods were successfully synthesized without any templates by calcining the alpha-FeOOH precursor in air at 300 degrees C for 2 h and their LPG sensing characteristics were investigated. The alpha-FeOOH precursor was prepared through a simple and low cost wet chemical route at low temperature (40 degrees C) using FeSO4 center dot 7H(2)O and CH3COONa as starting materials. The formation of alpha-FeOOH precursor and its topotactic transformation to alpha-Fe2O3 upon calcination was confirmed by X-ray diffraction measurement (XRD). X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) analysis. The alpha-Fe2O3 nanorods exhibited outstanding gas sensing characteristics such as, higher gas response (similar to 1746-50 ppm LPG at 300 degrees C), extremely rapid response (similar to 3-4 s), relatively slow recovery (similar to 8-9 min), excellent repeatability, good selectivity and lower operating temperature (similar to 300 degrees C). Furthermore, the alpha-Fe2O3 nanorods are able to detect up to 5 ppm for LPG with reasonable response (similar to 15) at the operating temperature of 300 degrees C and they can be reliably used to monitor the concentration of LPG over the range (5-60 ppm). The experimental results clearly demonstrate the potential of using the alpha-Fe2O3 nanorods as sensing material in the fabrication of LPG sensors. Plausible LP G sensing mechanism of the alpha-Fe2O3 nanorods is also discussed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: alpha-Fe2O3 nanorods; FESEM; LPG sensor; Semiconductor gas sensors; TEM; XPS; XRD

Facile room temperature methods for growing ultra thin films of graphene nanosheets, nanoparticulate tin oxide and preliminary assessment of graphene-tin oxide stacked layered composite structure for supercapacitor application - Patil, Sagar; Patil, Virendra; Sathaye, Shivaram; Patil, Kashinath (RSC Advances, 2014)
We report a novel, facile, single step process for growing highly uniform few layer graphene nanosheet (FLGNS) thin films over a micrometer scale, formed at the liquid-air interface. The process is further extended to form monolayer graphene nanosheets (GNS). The films are characterized by Raman spectroscopy, Atomic force microscopy (AFM) and X-ray photoelectron spectroscopy (XPS). The results indicate that very few chemical and/or physical defects are introduced during formation of films. Further, an innovative single step method to form tin oxide (SnO2) films at the liquid-air interface is presented. A special feature of the method is that entire process is completed at room temperature. The film can be suitably transferred to the desired substrates by Blodgett technique. Characterization by various techniques such as XPS, TEM and energy dispersive spectroscopy (EDS) shows that the films are made up of uniform spherical, crystalline SnO2 particles with the size in the range of 3-5 nm. Layer-by-layer (LbL) techniques can be exploited to stack graphene and SnO2 films alternately, in a desired sequence, forming a stacked composite structure. The composite structure is subjected to characterization by XPS, FE-SEM, TEM and EDS. The results show that the structure consists of a stack of predetermined thickness consisting of alternate layers of both the components. Such a structure is subjected to cyclic voltammetry (CV) studies. The results suggest LbL grown SnO2-GNS stacked composites exhibit better electrochemical performance in terms of specific capacitance and cycling ability which are primary requirements for the supercapacitor application. The coating techniques of few layer graphene nanosheets, SnO2 film and their stacked composite film are simple and inexpensive. A suitable explanation of the formation of both GNS and SnO2 films is discussed. The proposed methods extend the scope for production of high quality and defect free graphene nanosheets (GNS) and other components for forming LbL stacking of composite films.

Synthesis of silver nanoparticles colloids in imidazolium halide ionic liquids and their antibacterial activities for gram-positive and gram-negative bacteria - Patil, Virendra; Mahajan, Swapnil; Kulkarni, Mohan; Patil, Kashinath; Rode, Chandrashekhar; Coronas, Alberto; Yi, Gi-Ra (Chemosphere, 2020)
Four 1-butyl-3-methylimidazolium halide ionic liquids were synthesized via metathesis and anion exchange reactions. Silver nanoparticles (AgNPs) colloids were synthesized in four ionic liquids in the pressurized reactor by reduction of silver nitrate with hydrogen gas, without adding solvents or stabilizing agents. Antibacterial activities of base ionic liquids and AgNPs colloids in ionic liquids were reviewed by well-diffusion method for gram-positive Bacillus cereus (NCIM-2155) and gram-negative Escherichia coli (NCIM-2931) bacteria. Antibacterial activities of ionic liquids and AgNPs colloids in ionic liquids were observed to be controlled by ionic liquids anions and AgNPs particle size. The 1 -butyl-3-methylimidazolium iodide ionic liquid exhibited higher antibacterial activities among the studied ionic liquids. Further, the presence of AgNPs in 1-butyl-3-methylimidazolium iodide, ionic liquid enhanced its antibacterial activity for Bacillus cereus and Escherichia coli bacteria. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Anion effect; antibacterial activity; Imidazolium halides; ionic liquids; silver nanoparticles